Implementation of Academic Supervision in Improving Teacher Performance at SMK PGRI 2 Palembang - Agustina, Tri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study analyzes the implementation of academic supervision in improving teacher performance at SMK PGRI 2 Palembang. Using a systematic literature review, data were collected through article review. The results indicate that structured and continuous academic supervision positively impacts teacher performance. Key aspects such as constructive feedback, collaboration between school principals and teachers, and relevant training have proven effective in enhancing pedagogical competence and professionalism. The study recommends that schools continue to develop adaptive and responsive supervision programs to meet teachers’ needs, aiming for optimal learning outcomes for students. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. Thus, this research provides valuable insights for educational development at SMK.